2013
DOI: 10.4248/br201303001
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of the Blood Supply to Bone

Abstract: The importance of the vascular supply for bone is well-known to orthopaedists but is still rather overlooked within the wider field of skeletal research. Blood supplies oxygen, nutrients and regulatory factors to tissues, as well as removing metabolic waste products such as carbon dioxide and acid. Bone receives up to about 10% of cardiac output, and this blood supply permits a much higher degree of cellularity, remodelling and repair than is possible in cartilage, which is avascular. The blood supply to bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
219
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(250 citation statements)
references
References 145 publications
2
219
0
2
Order By: Relevance
“…As a consequence of this environment, the blood vessels in bone are highly active, not simply a passive source for the delivery of nutrients (2). Readers are referred to recent publications for more information about the active processes of the vasculature not covered in this review, including the vascular niche and hypoxia-driven signaling pathways (3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this environment, the blood vessels in bone are highly active, not simply a passive source for the delivery of nutrients (2). Readers are referred to recent publications for more information about the active processes of the vasculature not covered in this review, including the vascular niche and hypoxia-driven signaling pathways (3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…1). During torpor, thirteen-lined ground squirrels (Ictidomys tridecemlineatus) have adapted to prolonged periods of immobility, hypometabolism, hypothermia, and oxidative stress, each capable of reducing bone marrow activity (49,53). In one study, irradiation of hibernating ground squirrels showed a delay in bone marrow damage until after the animals had aroused (14).…”
mentioning
confidence: 99%
“…Although the vasculature does not indicate absolute oxygenation, it can give valuable insight into the oxygen availability in a particular region of the bone. As previously proposed [40], arteries enter the bone through the cortex, run centrally along the diaphysis and branch into smaller arterial vessels near the endosteal surface [41, 35]. Here arterial vessels give rise to sinusoids that coalesce as a central sinus at the center of the diaphysis.…”
Section: Hypoxia In the Bone Marrowmentioning
confidence: 91%